Workload, Work Discipline, and Organizational Commitment and Their Effects on Employee Performance: Evidence from PT Bonofactum, Bali - Ni Luh Pudak Sari; Made Ika Prastyadewi; Putu Pradiva Putra Salain (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Employee performance can be influenced by many factors such as workload, work discipline, and organizational commitment. Problems with employee performance have a significant impact on the sustainability of a company. There are many cases related to employee performance faced by PT. Bonofactum Kerobokan Badung. PT. Bonofactum Kerobokan Badung experiences fluctuations in production target achievement. This study aims to determine the effect of workload, work discipline, and organizational commitment on employee performance. The research method used is quantitative. The population used is PT. Bonofactum employees, and the sample size is 83 people. The results of the study show that workload, work discipline, and organizational commitment each have a negative and significant effect on employee performance. The researcher's suggestion is that PT. Bonofactum should review the number of work targets assigned to employees so that it can set more proportional work target policies that do not cause excessive burdens on employees, give warnings or sanctions to employees who arrive late without acceptable reasons, always appreciating every contribution made by employees to the company so that employees feel valued and motivated to remain committed to the organization, and periodically providing training to improve employees' abilities in meeting their daily/weekly work targets.